Malnutrition – Diarrhea Cycle: How to break this? - Umesh Patel; D Sharad Gedam (International Journal of Medical Research and Review, 2014)
In most of developing world Infectious diseases like acute gastroenteritis & Pneumonia are leading causes of Infant & Under five mortality. Malnutrition when present further increases morbidity & mortality of both diseases.